Parent and family perspectives on engagement: Lessons from the early years - Underwood, Kathryn; Killoran, Isabel (Canadian Journal of Education/Revue canadienne de l'éducation, 2013)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->This study identifies parent and family perspectives of the strengths of early years programs in three communities in Ontario, Canada. Using an Appreciative Inquiry approach, focus groups and surveys with parents, we investigate parent engagement and perceived outcomes of early years services in Ontario’s Best Start demonstration communities. The research study is grounded in the literature on family-centered practice, parent engagement and child outcomes from family participation. The major findings of the study include an extremely high rate of satisfaction with Best Start programs and services. Parents and families identify relationships with staff, access, and a wide range of programs as being critical for their engagement. In addition, the outcomes from early years programs and services go beyond child development and include direct benefits for the parents and families. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Keywords: Early years, parent engagement